POLA KOMUNIKASI ORGANISASI ANTAR KEPALA DESA DAN STAFF DI LOLOTUARA KABUPATEN MALUKU BARAT DAYA - Marleen Muskita; Rido Dominggus Latuheru; Hertina Claudia Mehratu (JURNAL BADATI, 2023)
In-depth interviews and literature review. The conclusion of this study is that judging from the communication process that occurs, it can be concluded that the effectiveness of a communication pattern used in the Lolotuara Village Office, Southwest Maluku Regency greatly influences the performance results of government staff in the village, this can be seen from the use of secondary communication patterns. , linear and circular which are quite good but the pattern of communication is primarily not implemented properly so that the performance of the staff in the office has not been done optimally. It is hoped that all parties can carry out their duties and responsibilities to the fullest, and the communication patterns that occur within the Lolotauara Village office environment will continue to be even better, so as to create a sense of mutual understanding. Positive feedback and effective communication patterns can also be realized as expected by all parties.